A computer-assisted system for handheld whole-breast ultrasonography - Šroubek, Filip; Bartoš, Michal; Schier, Jan; Bílková, Zuzana; Zitová, Barbara; Vydra, Jan; Macová, Iva; Daneš, Jan; Lambert, Lukáš (International journal of computer assisted radiology and surgery, 2019)
PURPOSE: Breast ultrasonography (US) presents an alternative to mammography in young asymptomatic individuals and a complementary examination in screening of women with dense breasts. Handheld US is the standard-of-care, yet when used in whole-breast examination, no effort has been devoted to monitoring breast coverage and missed regions, which is the purpose of this study. METHODS: We introduce a computer-aided system assisting radiologists and US technologists in covering the whole breast with minimum alteration to the standard workflow. The proposed system comprises a standard US device, proprietary electromagnetic 3D tracking technology and software that combines US visual and tracking data to estimate a probe trajectory, total time spent in different breast segments, and a map of missed regions. A case study, which involved four radiologists (two junior and two senior) performing whole-breast ultrasound in 75 asymptomatic patients, was conducted to test the importance and relevance of the system. RESULTS: The mean process time per breast was [Formula: see text], with no statistically significant difference between the left and the right sides, and slightly longer examination time of junior radiologists. The process time density shows that central parts of the breast have better coverage compared to the periphery. Within the central part, missed regions of minimum detectable size of [Formula: see text] occur in [Formula: see text] of examinations, and non-negligible [Formula: see text] regions occur in [Formula: see text] of cases. CONCLUSION: The results of the case study indicate that missed regions are present in handheld whole-breast US, which renders the proposed system for tracking the probe position during examination a valuable tool for monitoring coverage.
Keywords: Software; Coverage; Cancer; software; Diagnosis, Computer-Assisted; Humans; lidé středního věku; diagnóza počítačová; Ultrasound; Equipment Design; Female; Ultrasonography, Mammary; dospělí; Breast; Tracking; počítačové systémy; lidé; počítače do ruky; počítačové zpracování obrazu; Computers, Handheld; Image Processing, Computer-Assisted; reprodukovatelnost výsledků; mamografie; Adult; Breast Neoplasms; ženské pohlaví; Reproducibility of Results; Middle Aged; ultrasonografie prsů; Screening; design vybavení; Computer Systems; nádory prsu; Mammography; prsy